2003
DOI: 10.1074/jbc.m300205200
|View full text |Cite
|
Sign up to set email alerts
|

PP2A Activation by β2-Adrenergic Receptor Agonists

Abstract: Understanding the mechanisms that regulate cell migration is important for devising novel therapies to control metastasis or enhance wound healing. Previously, we demonstrated that ␤ 2 -adrenergic receptor (␤ 2 -AR) activation in keratinocytes inhibited their migration by decreasing the phosphorylation of a critical promigratory signaling component, the extracellular signal-related kinase (ERK). Here we demonstrate that ␤ 2 -ARinduced inhibition of migration is mediated by the activation of the serine/threonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 91 publications
1
42
0
Order By: Relevance
“…Moreover, several studies have confirmed a role for PP2A in the control of cell migration. 123,124 Finally, proteomic analyses have identified SET in complex with a host of cellular proteins including the Rac/Cdc42 GEF βPIX and the Rac/Cdc42 effector PAK1, 125 actin and dynamin-2 119 and a β1-integrin-filamin complex. 126 A recent study by Switzer et al 127 showed that a SET-binding peptide (COG112) does not only block the Rac1-SET interaction, but also reduces EGF-induced Rac1 activation and serum-induced cell migration and invasion.…”
mentioning
confidence: 99%
“…Moreover, several studies have confirmed a role for PP2A in the control of cell migration. 123,124 Finally, proteomic analyses have identified SET in complex with a host of cellular proteins including the Rac/Cdc42 GEF βPIX and the Rac/Cdc42 effector PAK1, 125 actin and dynamin-2 119 and a β1-integrin-filamin complex. 126 A recent study by Switzer et al 127 showed that a SET-binding peptide (COG112) does not only block the Rac1-SET interaction, but also reduces EGF-induced Rac1 activation and serum-induced cell migration and invasion.…”
mentioning
confidence: 99%
“…Finally, we demonstrate that keratinocytes express protein for two key enzymes in the catecholamine synthesis cascade localized to cytoplasmic granules and measure epinephrine in keratinocyte extracts. We believe that this is the first demonstration that ␤-AR antagonists can accelerate human skin wound re-epithelialization, and we hypothesize that the mechanism of action is via blockade of an endogenous autocrine ␤2-AR network that slows migration and delays wound healing (33,34).…”
Section: Discussionmentioning
confidence: 83%
“…Upon mechanical injury of confluent keratinocyte cultures (42) or Madin-Darby canine kidney cell cultures (43), ERK is activated by and is required for wound repair in confluent rat keratinocyte cultures (63) and in human epidermis (64). Previously, we have demonstrated that phospho-ERK is localized at the lamellipodial edge in migrating keratinocytes (33) and that ␤-AR agonists decrease ERK phosphorylation and prevent its localization to the lamellipodia via protein phosphatase 2A-dependent mechanisms (33,34). Although the function of phospho-ERK at the lamellipodial edge is unknown, it is possible that direct interactions between ERK and ␤ integrins (65) or paxillin (66) take place, suggesting an important role for ERK in integrating cell adhesion and receptor-mediated signaling in the control of cell migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PP2A is one of the major phosphatases involved in GPCR dephosphorylation (25). It binds directly to intracellular domains of the chemokine receptor CXCR2 (33) and the metabotropic glutamate receptor 5 (34) and co-immunoprecipitates with the ␤2-adrenergic receptor (35). In HEK293 cells stably expressing the CXCR2 receptor, inhibition of PP2A by okadaic acid increases basal phosphorylation of the CXCR2 receptor and reduces the increase in intracellular calcium concentration after a short-term stimulation with the agonist CXCL8 (33).…”
Section: Discussionmentioning
confidence: 99%